Dispersal strategies, rapid geographic range expansion and their effects on invasive European starlings, Sturnus vulgaris, in South Africa and Australia - Phair, David James (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.